Study Of Mathematical Modeling Of Control System For Continuous Stirred Tank Reactor - Muhammad Hakimi b Abdullah Zamawi, Muhammad Hakimi (2010)
This simulation-based approach for this project is to provide better understanding of plant model design and enabling me to optimize the design to meet predefined performance criteria.